A novel one-step method for oil-rich biomass production and harvesting by co-cultivating microalgae with filamentous fungi in molasses wastewater. (March 2019) - Yang, Limin; Li, Huankai; Wang, Qin
Highlights: Co-cultivation of microalgae with fungi performed well in wastewater remediation. Co-cultivation assisted harvesting is a good way for biomass production and harvest. Microalgal-fungal biomass might be a good feedstock for biodiesel production. Abstract: Aiming at simplifying the harvesting procedure, reducing the production cost, and improving the quality of microalgae-based biodiesel, herein, a novel one-step method for oil-rich biomass production and harvesting was proposed by growing Chlorella sp. with Aspergillus sp. in molasses wastewater. Lipid content and fatty acid profile were measured to assess the suitability of microalgal-fungal biomass for biodiesel production. The results showed that the highest biomass yield (4.215 g/L) was obtained when the inoculation ratio of fungi and microalgae was 100. Activities of fungi positive impacted the decolorization of wastewater and the removal of suspended solids. Thus, co-cultivation system had better performance than mono-system of microalgae in the removal of nutrients in wastewater. Analysis of biomass compositions showed that compared with mono-system of microalgae, co-cultivation system produced biomass with higher lipid content (35.2%) and yield microbial cell oil with lower unsaturation degree, potentially increasing the quality of microbial-cell-lipid based biodiesel.